FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI KASUS 2013 – 2015) - Misbahuddin Misbahuddin (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of this research is to know additional information about the influence of Rasioprofitability (Net Profit Margin (NPM), Earning per Share (EPS), Return on Assets (ROA), and Return on Equity (ROE) to stock price either significantly presented simultaneously and partially, the research method used is multiple regression analysis The results of this study Simultaneously proved that Net Profit Margin (NPM), Earning Per Share (EPS), Return on Assets (ROA), and Return on Equity (ROE) a significant influence on stock prices while Partially proved that the Return OnEquity (ROE) has a significant negative effect on stock prices, this is possible because in assessing the company, investors are still considering the company's ability to provide returns on shareholders. In addition, partially proven that Earning Per Share (EPS) has a significant positive effect on stock prices, this is possible because the Earning Per Share (EPS) produced contains good information dilitinjau of the stock price as a reflection of the performance of a company, the higher stock prices, indicating the better performance of the company. or in other words its performance is also good.